Hubungan Kepatuhan Antiretroviral Therapy Dengan Status Gizi Dan Kadar CD4 Pada Anak HIV/AIDS - Ninuk Dahliyanti; Rahayu Khairiah; Nuraidah; Farida Murtiani (Jurnal Kesehatan Komunitas, 2022)
Children living with Human Immunodeficiency Virus (HIV) face many challenges, one of which is taking antiretroviral (ART) every day for life to reduce the amount of virus. This study aims to determine the relationship between ART adherence with nutritional status and CD4 in children with HIV/AIDS at RSPI Prof. Dr. Sulianti Saroso. This study was quantitative research with cross sectional design. Samples of all HIV/AIDS child patients with ART treatment and taking ARV drugs at RSPI Prof. Dr. Sulianti Saroso totaling 56 people in 2021 were taken using a total sampling technique. Secondary data sources in this study were obtained from reports of Pokja HIV/AIDS and medical records, data analysis used chi square test (univariate and bivariate data). The results showed that of the 56 respondents, most of them 48 (85.7%) adhered to ART treatment, 43 (76.8%) had good nutritional status, 46 (82.1%) were in good CD4 category (> 500 cells/mm3). There is a relationship between adherence to ART treatment with nutritional status (p value = 0.012 < alpha 5%). There was a relationship between ART treatment adherence and CD4 cell count (p value = 0.003 < alpha 5%). ART adherence is related to nutritional status and CD4 cell count in HIV/AIDS children.